Metabolic Effects of Oestrogen Treatment in Patients with Carcinoma of Prostate: A Comparison of Stilboestrol and Conjugated Equine Oestrogens - Shahmanesh, M. (1973)
Serum cholesterol and triglyceride levels were estimated and oral glucose tolerance tests performed on 16 patients with carcinoma of the prostate before treatment and while receiving stilboestrol in doses of 1 mg, 7·5 mg, and 15 mg daily and conjugated equine oestrogens (Premarin) 15 mg daily. Serum triglyceride levels were greater than 170 mg/100 ml in nearly all the patients while receiving Premarin or stilboestrol 7·5 mg and 15 mg daily. In six out of 10 patients who were given stilboestrol 1 mg daily the serum triglycerides remained within the normal range. No significant effects on serum cholesterol levels or glucose tolerance tests were observed with the various oestrogen regimens. The results support previous suggestions that a daily dose of 1 mg of stilboestrol should be regularly used in the treatment of carcinoma of the prostate.